A Noble Fight : African American Freemasonry and the Struggle for Democracy in America - Walker, Corey D. B. (Book collections on Project MUSE., 2008)
"A Noble Fight examines the metaphors and meanings behind the African American appropriation of the culture, ritual, and institution of freemasonry in navigating the contested terrain of American democracy. Combining cultural and political theory with extensive archival research--including the discovery of a rare collection of nineteenth-century records of an African American Freemason Lodge--Corey D.B. Walker provides an innovative perspective on American politics and society during the long transition from slavery to freedom."--Jacket.